2015
DOI: 10.4321/s0211-95362015000100006
|View full text |Cite
|
Sign up to set email alerts
|

The role of the media in influencing public attitudes to penicillin during World War II

Abstract: SUMMARY: 1.-Penicillin and the public consciousness. 2.-Alternative penicillin. 3.-Publicity control and conclusions ABSTRACT: Penicillin's trajectory towards becoming an effective antibacterial chemotherapeutic agent took place during World War II. Its strategic military value was immediately recognised by the Allies, and mass production was undertaken with the prime objective of meeting the needs of the armed forces. News of its development came to be widely reported on in the media and is examined here. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Another plasmid mediated quinolone resistance gene is aac (6')-Ib-cr, which encodes aminoglycoside acetyltransferase enzyme. This enzyme which can diminish a fluoroquinolone activity by adding an acetyl group to this antibiotic (Ramirez and Tolmasky, 2017) Sulfa drugs are an important class of synthetic bacteriostatic antibiotics still used today for the treatment of bacterial infections and those caused by other microorganisms, sulfa drugs achieve this bacteriostatic action by inhibiting the synthesis of folic acid in bacteria (Shama, 2015). They are also known as sulfa drugs and were the main source of therapy against bacterial infections before the introduction of penicillin in 1941.…”
Section: Discussionmentioning
confidence: 99%
“…Another plasmid mediated quinolone resistance gene is aac (6')-Ib-cr, which encodes aminoglycoside acetyltransferase enzyme. This enzyme which can diminish a fluoroquinolone activity by adding an acetyl group to this antibiotic (Ramirez and Tolmasky, 2017) Sulfa drugs are an important class of synthetic bacteriostatic antibiotics still used today for the treatment of bacterial infections and those caused by other microorganisms, sulfa drugs achieve this bacteriostatic action by inhibiting the synthesis of folic acid in bacteria (Shama, 2015). They are also known as sulfa drugs and were the main source of therapy against bacterial infections before the introduction of penicillin in 1941.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of penicillin by Sir Alexander Fleming (1928) can be viewed as a prime example of such discoveries that introduced therapies to treat staphylococcal and streptococcal infections and modulate blood coagulation 67. Penicillin got worldwide recognition due to the inventor's seminal works published by highly prestigious and widely visible British journals, effective ‘real-world’ antibiotic therapy of pneumonia and wounds during World War II, and euphoric media coverage 8. In 1945, Fleming, Florey and Chain got a much deserved Nobel Prize in Physiology or Medicine for the discovery that led to the mass production of the wonder drug in the U.S. and ‘real-world practice’ that tested the use of penicillin.…”
Section: Examples Of Influential Scientific Hypothesesmentioning
confidence: 99%
“…To do so he had first to separate the mold biomass from the broths in which the mold was cultured, and, in his own words, "for convenience and to avoid repetition of the cumbersome phrase 'mould broth filtrate' the name 'penicillin' will be used." 64 An assessment of this act of Fleming's made by the botanist Jules Brunel in 1944-a time during the Second World War when media interest in penicillin was at its peak 65 -is worthy of consideration here. 66 showed that some species produced "penicillin-like substances" and that furthermore, certain species were able to produce more than one antibiotic simultaneously.…”
Section: Antibacterial Compounds Produced By the Penicilliamentioning
confidence: 99%